2022
DOI: 10.3389/fpsyg.2022.760146
|View full text |Cite
|
Sign up to set email alerts
|

The Joint Effects of Social Norm Appeals and Fear Appeals in COVID-19 Vaccine Campaign Posters on Self-Perceived Communication Quality and Vaccination Intention

Abstract: To understand how different types of cues in vaccine education messages affect attitude toward campaign messages and vaccination intention, this study examined the impact of the presence of social norm appeals (individual vs. group cues) and the presence of fear appeals in coronavirus disease 2019 (COVID-19) vaccine campaign posters on perceived communication quality and vaccination intention. A 2 (social norm appeal: individual cue vs. group cue) × 2 (fear appeal: absence vs. presence) × 3 (repetition) within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Hing et al [ 22 ] reported a backfire effect of a negative attribute framing to influence COVID-19 vaccination intentions among Malaysian adults. Similarly, Liu et al [ 29 ] showed that the presence of fear appeals in COVID-19 vaccine campaign posters elicited lower levels of vaccination intentions among Chinese adults than those without fear appeals. Also, the loss frame was less effective in motivating people to vaccinate against COVID-19 than the gain frame among Chinese college students [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hing et al [ 22 ] reported a backfire effect of a negative attribute framing to influence COVID-19 vaccination intentions among Malaysian adults. Similarly, Liu et al [ 29 ] showed that the presence of fear appeals in COVID-19 vaccine campaign posters elicited lower levels of vaccination intentions among Chinese adults than those without fear appeals. Also, the loss frame was less effective in motivating people to vaccinate against COVID-19 than the gain frame among Chinese college students [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, the scholars recommend using communication to address COVID-19 vaccine hesitancy [ 10 ]. While information-based messages are necessary [ 20 , 21 ], using narrative messages that convey positive experiences and emotions can help create closer links between people and health [ 62 ], rather than using messages appealing to fear which the evidence shows do not always encourage people to get vaccinated [ 63 ]. The effects of the COVID-19 pandemic generated high emotional and mental health distress [ 64 ] which made using vaccination messages appealing to negative emotions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…8 This finding is in line with the finding from an experiment in which participants received messages with fear appeals and a higher level of willingness to get the COVID-19 vaccine resulted. 9 One of the most prominent theoretical frameworks related to fear appeals is the extended parallel process model (EPPM). 10…”
Section: Purposementioning
confidence: 99%
“…8 This finding is in line with the finding from an experiment in which participants received messages with fear appeals and a higher level of willingness to get the COVID-19 vaccine resulted. 9 One of the most prominent theoretical frameworks related to fear appeals is the extended parallel process model (EPPM). 10 EPPM explains possible responses to fear-based messages 11 and posits that individuals will appraise various messages, which leads to two distinct processes-the fear control process and the danger control process.…”
mentioning
confidence: 99%